Evaluation of neem based formulations and chemical fungicides for the management of sorghum leaf blight - K. MATHUR, R.N. BUNKER* and (Indian Phytopathology, 2008)
Four neem based formulations, namely, neem seed extract, neem oil, Azadirachtin and Achook each at 0.2 per cent (V/V) and five fungicides - mancozeb, carbendazim, thiabendazole, thiophanate methyl and captan @ 50 to 1000 ppm were evaluated in-vitro against sorghum leaf blight pathogen Exserohilum turcicum. The effective ones -neem seed extract, carbendazim and mancozeb, were then evaluated in the field as seed treatment, spray or combination of both, on leaf blight susceptible hybrid CSH-14, under inoculations of E. turcicum. The treatments were more effective when applied in combination of seed treatment and spray in controlling the disease and enhancing grain and fodder yield.